When do product architectures mirror organisational architectures? The combined role of product complexity and the rate of technological change - Burton, N.; Galvin, Peter (2018)
© 2018 Informa UK Limited, trading as Taylor & Francis Group In the modularity literature, an architectural decomposition and ‘mirroring’ between task boundaries, knowledge boundaries, and firm boundaries has been suggested as a way to enhance managerial efficiency and as a source of potential strategic advantage. Despite its intuitive appeal, empirical support for ‘mirroring’ is significant but mixed. In this paper, we utilise an industrial economics and knowledge-based perspective to hypothesise how the combined effects of product architecture type, product complexity and the rate of product component change may influence task, knowledge and firm boundaries and hence be associated with either phases of mirroring or non-mirroring (‘misting’). We suggest that whether mirroring or misting is an efficient strategic choice is influenced by the characteristics of both the product architecture and the rate of technological change at the product component level, and changes across time as products evolve. Our framework helps to reconcile existing mixed evidence and provides the foundation for further empirical research.